(untitled) (International Journal of Physiotherapy, 2014)
Background: Stroke is an acute onset of neurological dysfunction resulting in the most common disability. Balance among these stroke subjects is impaired. To determine the effect of task oriented exercises on standing balance in subjects with stroke using performance oriented tinetti assessment score and single leg stance time is the need if the study. Methods: Participants were taken from outpatient department of physiotherapy and neurology department in the institute. Randomized controlled trial with Prospective experimental design with simple random sampling including 30 subjects. An inclusion criterion includes stroke subjects with age 40- 75, both genders who were confirmed as stroke subjects by MRI n CT scan investigations. Right or left hemiplegia who are conscious and coherent were included. Subjects with spinal injuries, cognitive, perceptual disorders, shoulder subluxations, cardiac problems were excluded. Participants received daily 45 minutes of task oriented exercises protocol for 6days a week for 6weeks for study group and conventional physiotherapy for control group. Results: Performance oriented tinetti assessment score and Single leg stance time which is valid and reliable measure for balance in stroke subjects was used. There is a significant improvement in performance oriented tinetti assessment score and single leg stance time from baseline to the end of intervention with significance (P<0.01) existing between the baseline and 6th week in both variables. Conclusion: Task oriented exercises appeared effective in improving standing balance in subjects with stroke. Single leg stance duration improved on task oriented exercise approach.